UNIVERSALITY OF HUMAN RIGHTS: A CROSS-CULTURA ANALYSIS - Makeieva, Olena; Rybikova, Hanna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose: to analyze from a theoretical and legal point of view the modern problems that exist in the process of cognition and comprehension of the principle of universality of human rights. Research methods: the dialectical method of cognition, general scientific and special methods, in particular cross-cultural analysis, were used in the work. Results: it has been found that international human rights standards are universal, they are endowed with universalism, which can be considered in two aspects: firstly, they apply to all people without exception, regardless of any characteristics, which is reflected in many legal documents (subjective criterion); secondly, referring to the developed terminology, from the point of view of the scope of rights (standards), they are also usually differentiated into two groups: universal and regional (territorial criterion). It has been established that to some extent there has been a decrease in the general belief in the possibility of progress of humanity towards universal values on the basis of globalization. Discussion: if earlier the universality of human rights was a more or less obvious idea within the framework of Kant’s project of perpetual peace, and cultural differences acted as an additional factor, today the very justification of the universality of such rights becomes more problematic. Human rights are a kind of individual rights from which a person cannot waive, and the achievement of which is a goal on a global scale. Human rights, unlike other rights, always retain their validity, even if they do not belong to treaties and constitutions. However, their implementation requires institutionalization. Universal human rights standards are enshrined in universal international legal acts adopted by all or most countries of the world, and apply to the entire population of the Earth, primarily related to the activities of the United Nations.